Neuropeptide Y and Calcitonin Gene-Related Peptide in Cerebrospinal Fluid in Parkinson’s Disease with Comorbid Depression versus Patients with Major Depressive Disorder - Svenningsson, Per; Pålhagen, Sven; Mathé, Aleksander A. (Frontiers in Psychiatry, 2017)
Parkinson’s disease (PD) is the second most common neurodegenerative disease in the world. The diagnosis of PD is based on movement dysfunctions. Many patients also suffer from co-morbid depression in spite of adequate treatment with dopamine replacement, indicating that also other, non-dopaminergic mechanisms are involved. Indeed, neuropeptides are critically implicated in the pathophysiology of major depressive disorder (MDD). To increase our understanding of the biochemical basis of depression in PD patients, we examined the levels of neuropeptide Y (NPY) and calcitonin gene-related peptide (CGRP) in cerebrospinal fluid (CSF) from PD patients, with or without co-morbid depression, and compared them to the levels in patients with MDD. We also compared the levels of NPY and CGRP with 5-hydroxyindoleacetic acid (5-HIAA), the major serotonin metabolite. Both NPY and CGRP were higher in PD patients with co-morbid depression compared to MDD patients No similar difference was found in 5-HIAA levels. Accordingly, there were no correlations between NPY and 5-HIAA or CGRP and 5-HIAA levels. The finding of higher NPY and CGRP CSF levels in PD patients with MDD raise the possibility that different pathophysiological processes may underlie depression in PD and MDD.